2021
DOI: 10.1177/21501327211044058
|View full text |Cite
|
Sign up to set email alerts
|

The Care-of-the-Elderly Health Guide

Abstract: Introduction: The Evidence-Based Care of the Elderly Health Guide is a clinical guide with cross-references for care recommendations. This guide is an innovative adaptation of the Rourke Baby Record to support elderly care. In 2003, the guide was published with an endorsement from the Health Care-of-the-Elderly Committee of the College of Family Physicians of Canada. Since then, physicians have used the guide as a checklist and a monitoring tool for care to elderly patients. Objective: We will update the 2003 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…From last decade, caring for elderly patients has drawn increasing attention in multiple clinical settings, including CAP. 9 Aging-care factors comprise various clinical parameters such as functional status, frailty assessment, comorbidities, and nutritional assessment. 10 Previous studies have shown that aging-care relevant parameters, such as functional status, comorbidities, malnutrition and frail, are strongly associated with poor prognosis in CAP patients.…”
Section: Introductionmentioning
confidence: 99%
“…From last decade, caring for elderly patients has drawn increasing attention in multiple clinical settings, including CAP. 9 Aging-care factors comprise various clinical parameters such as functional status, frailty assessment, comorbidities, and nutritional assessment. 10 Previous studies have shown that aging-care relevant parameters, such as functional status, comorbidities, malnutrition and frail, are strongly associated with poor prognosis in CAP patients.…”
Section: Introductionmentioning
confidence: 99%